Identification and genotoxicity evaluation of potential impurities in rabeprazole sodium using in silico and in vitro analyses. (3rd September 2022) - Du, Yi; Wu, Yinnan; Liu, Yang; Meng, Changhong; Tan, Li; Cai, Tiantian; Wang, Yuxin; Lu, Yihong
Abstract: Rabeprazole sodium is a widely used drug for gastrointestinal disorders. Several analytical methods for identifying rabeprazole sodium and its impurities have been reported. However, the genotoxicity of rabeprazole sodium and its impurities is still unclear. Thus, it is necessary to develop analytical methods that can identify the structures of its impurities and evaluate their genotoxicity. Here, we used high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry for identifying the impurities in rabeprazole sodium enteric-coated tablets. Impurities in the samples were matched with synthesized impurities based on the exact mass and secondary mass spectrometry characteristics and then subjected to in silico analysis using the Derek and Sarah software, as well as in vitro genotoxicity evaluations. Our method successfully identified the impurities as 2-[[4-(3-methoxy propane)-3-methyl-N-oxido-2-pyridyl] methyl sulfonyl]-1H-benzimidazole (impurity I), 2-[[4-(3-methoxy propane)-3-methyl-2-pyridyl]methyl sulfonyl]-benzimidazole (impurity II), 2-[[4-(3-methoxy propane)-3-methyl-2-pyridyl] methionyl]-1H-benzimidazole (impurity III), and 2-mercapto benzimidazole (impurity IV). In silico analysis predicted that impurity III demonstrated a structural alert; thus, this impurity was evaluated for in vitro genotoxicity using the Ames test and chromosomal aberration assay. Impurity III at concentrations of 7.5–30 μg/mL had an aberration rate of over 5% with or without S-9 mix. Furthermore, impurity III at concentrations of 40–1000 μg/plate significantly increased the number of mutagenic colonies with or without S-9 mix. These results indicated that impurity III should be regulated to the limit of 0.01%.